If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 = -4p Solving 64 = -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. 64 + 4p = -4p + 4p Combine like terms: -4p + 4p = 0 64 + 4p = 0 Add '-64' to each side of the equation. 64 + -64 + 4p = 0 + -64 Combine like terms: 64 + -64 = 0 0 + 4p = 0 + -64 4p = 0 + -64 Combine like terms: 0 + -64 = -64 4p = -64 Divide each side by '4'. p = -16 Simplifying p = -16
| 2(x+3)(x+3)-5=14x+17 | | (x*11)+(y*9)=360 | | 8j=40 | | x^2-12x+27=2x^2-12x+18 | | 7r^2+36r+5=0 | | 8r^4+32r^2+32=0 | | 16x+1.0625x= | | 2x+6-4(x+1)=5x+6 | | =2c+5 | | (4x+1)(x+1)=0 | | 7x^2+12x=-2 | | f(7x)=3x^2+2 | | 2x+8-4(x+1)=3x+7 | | y=16*5 | | 9x-2+5= | | 49x^4+126x^2+81=0 | | 3x^2+31x-10=0 | | x+5=8x-6 | | -2x-3y=-24 | | 2(5x^2-50)=0 | | -10x-(5-4x)= | | 6x+2x+8=x+15 | | 14r=77 | | 3x^2-11x-9=x^2+6x-x(x+1)+1 | | b^2+12+c=0 | | 6(x+y)=x | | 0.86x+0.9(12-x)=10.56 | | 6+18/3*4= | | V=Ihw | | 1.5y=45 | | -30+5x-8x=42 | | 5s-10=92.05 |